PENERAPAN METODE SAFETY STOCK PADA SISTEM INVENTARIS SEKOLAH DASAR NEGERI DI KECAMATAN BARENG BERBASIS WEBSITE - Wafiq Nur Latifah; Aries Dwi Indriyanti; Zein Vitadiar, Tanhella; Didiek Rusdyanto (Inovate, 2024)
The increasingly rapid development of technology forces human life to follow every development, one ofwhich is the existence of computers which have become the main commodity in every activity. Advancesin technology and information also provide many conveniences in processing inventory data. Oneimportant aspect in an institution is the management of inventory items, because they are assets of theinstitution whose existence and condition must always be monitored and reported at all times. With thisreport, information regarding the presence or absence of an inventory item can be obtained. The goodsinventory system in public elementary schools in Bareng sub-district is not yet optimal regarding inventoryrecording reports and there is a lack of order in reporting inventory items. This research aims to design andimplement a website-based school inventory system using the Safety Stock method to increase theefficiency of school inventory items. This method prioritizes securing school inventory stock so that thereare no shortages when requested at each institution. The research results show that the application of theSafety Stock method is effective in managing school inventory in public elementary schools in Bareng sub-district, with a significant reduction in the waiting time for inventory items to arrive and the completiontime for school inventory reports. This system provides an efficient solution to improve the quality of theschool inventory security system and operational reports in each institution in the Bareng sub-district.Keywords: Inventory, Safety Stock, School.